2021
DOI: 10.1101/2021.03.25.21254087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prenatal smoking, alcohol and caffeine exposure and maternal reported ADHD symptoms in childhood: triangulation of evidence using negative control and polygenic risk score analyses

Abstract: Background and aims: Several studies have indicated that maternal prenatal substance use may be associated with offspring ADHD via intrauterine effects. We investigated associations between maternal prenatal smoking, alcohol and caffeine consumption with childhood ADHD risk accounting for shared familial factors. Design: First, we used a negative control design comparing maternal and paternal substance use. Three models were used for negative control analyses: unadjusted (without confounders); adjusted (inclu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 68 publications
3
8
2
Order By: Relevance
“…We used maternal and offspring variants in the ADH and ALDH genes linked to alcohol use and metabolism to investigate whether there is a causal effect of fetal alcohol exposure on childhood ADHD risk. Consistently with previous work, we did not find evidence for a causal effect (Haan et al, 2021). We observed only weak evidence in one cohort (MoBa) of a negative association between maternal GRS and maternal reported offspring symptoms, in the hyperactivity domain only.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We used maternal and offspring variants in the ADH and ALDH genes linked to alcohol use and metabolism to investigate whether there is a causal effect of fetal alcohol exposure on childhood ADHD risk. Consistently with previous work, we did not find evidence for a causal effect (Haan et al, 2021). We observed only weak evidence in one cohort (MoBa) of a negative association between maternal GRS and maternal reported offspring symptoms, in the hyperactivity domain only.…”
Section: Discussionsupporting
confidence: 92%
“…This is not unexpected, as several studies had previously shown informant discrepancies in the assessment of children mental health problems which may be affected by factors such as mothers own mental health and socioeconomic status (Collishaw et al, 2009; De Los Reyes and Kazdin, 2005). Different findings in previous studies and our study may be also related to scales used for ADHD symptom assessment as observed in our previous study (Haan et al, 2021) and the study by Eilertsen and colleagues. The child’s age at the time of assessment and severity of the ADHD symptoms may as well have an impact on the observed results.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations